(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of finish lines obtained using an intraoral scanner and to analyze associated factors at Hai Phong University of Medicine and Pharmacy Hospital. Methods: A cross-sectional descriptive study was conducted on 207 abutment teeth from 48 patients requiring crown restorations (October 2025 – March 2026). Impressions were taken using a Medit i700 intraoral scanner and analyzed with Medit Link software. Associated factors included tooth position, jaw location, and clinician’s clinical experience (< 5 years vs. ≥ 5 years). Data were analyzed using Chi-square (χ²) and ANOVA tests (p < 0.05). Results: The chamfer finish line was most prevalent (58.0%), followed by shoulder (25.6%) and sloped (knife‑edge) finish lines (16.4%). Mean finish line width was 0.83 ± 0.24 mm, and mean emergence angle was 128.5 ± 9.2°. Subgingival finish lines accounted for the highest proportion (35.7%). Finish line position relative to the gingiva was significantly associated with tooth group (p < 0.001) and finish line type (p = 0.042). The choice of finish line type was not significantly associated with clinician experience (p > 0.05). Conclusion: Scan data revealed that chamfer finish lines and subgingival margins predominated, particularly in anterior teeth.